Chloride ions formation during degradation of organochloride compounds using TiO2 deposited on glass microspheres - Dabrowski, B; Zaleska, A; Hupka, J (Central European journal of public health, 2000)
Aqueous solutions containing 200 mg/dm3 of p,p'-DDT and methoxychlor were photodegraded for 60 min in UV/TiO2/O2 system and chloride ions concentration and pH were measured. From 60 to 80% of the investigated pesticides were eliminated after treatment. Over 27% of chlorine atoms were splitted off for methoxychlor and 10% for p,p'-DDT. The experimental data suggest, that chlorine atoms were removed from the -CCl3 moiety but the chlorine atoms bound to aromatic ring were left intact at this step of photodegradation.
Keywords: chloridy; mikrosféry; insekticidy; DDT; Kinetics; Titanium; Methoxychlor; Microspheres; kinetika; Chlorides; methoxychlor; Insecticides; titan